2010
DOI: 10.3109/03639041003657295
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol bioavailability after nasal and transdermal application: effect of permeation enhancers

Abstract: The results of this study indicated that CBD could be successfully delivered through the IN and transdermal routes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 35 publications
2
85
0
Order By: Relevance
“…Furthermore, transdermal delivery of other medications, such as naltrexone and acamprosate, could enhance the utility of pharmacotherapy based treatments for alcohol dependence in general. Transdermal delivery is a controllable extended release formulation (Paudel et al , 2010), therefore improves patient compliance because medications can be administered less frequently. Additionally, transdermal products are non-invasive which promotes patient friendly usage, in contrast to injectable formulations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, transdermal delivery of other medications, such as naltrexone and acamprosate, could enhance the utility of pharmacotherapy based treatments for alcohol dependence in general. Transdermal delivery is a controllable extended release formulation (Paudel et al , 2010), therefore improves patient compliance because medications can be administered less frequently. Additionally, transdermal products are non-invasive which promotes patient friendly usage, in contrast to injectable formulations.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 250 μL of blood was collected and placed into silanized microcentrifuge tubes containing heparin, centrifuged at 10,000 × g for 3 min and plasma was stored at −70°C until quantification by LC-MS. CBD was extracted according to previously described methods (Paudel et al , 2010). Briefly, CBD was extracted from 50 μL of plasma using 500 μL of acetonitrile (ACN):ethyl acetate (1:1, v/v).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This selective targeting of KSHV-induced neoplasia suggests that CBD may have a desirable therapeutic index when used to treat cancer. Moreover, a recent study demonstrated that CBD can be delivered effectively by nasal and transdermal routes, 46 which may be particularly valuable for the treatment of Kaposi sarcoma oral or skin lesions. 47 The molecular mechanisms by which CBD exerts its therapeutic effects are not fully understood, although CBD has been shown to act as an inverse agonist of the cannabinoid receptors CB1 and CB2.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabis typically has a moderate analgesic effect, and may function best when used synergistically with opioids for pain control . Paudel showed CBD delivery for chronic, extended use could be done via transdermal methods, whereas CBD use for breakthrough pain could be achieved using an intranasal method, allowing for a more rapid onset of approximately 10 minutes . The mortality and morbidity associated with narcotic use for pain control continues to be a serious concern for physicians.…”
Section: Potential Therapies For the Otolaryngic Patientmentioning
confidence: 99%